Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.